Simple fluorescence‐based high throughput cell viability assay for filamentous fungi. (1st September 2015) - Chadha, S.; Kale, S.P.
Abstract: Filamentous fungi are important model organisms to understand the eukaryotic process and have been frequently exploited in research and industry. These fungi are also causative agents of serious diseases in plants and humans. Disease management strategies include in vitro susceptibility testing of the fungal pathogens to environmental conditions and antifungal agents. Conventional methods used for antifungal susceptibilities are cumbersome, time‐consuming and are not suitable for a large‐scale analysis. Here, we report a rapid, high throughput microplate‐based fluorescence method for investigating the toxicity of antifungal and stress (osmotic, salt and oxidative) agents on Magnaporthe oryzae and compared it with agar dilution method. This bioassay is optimized for the resazurin reduction to fluorescent resorufin by the fungal hyphae. Resazurin bioassay showed inhibitory rates and IC50 values comparable to the agar dilution method and to previously reported IC50 or MICs for M. oryzae and other fungi. The present method can screen range of test agents from different chemical classes with different modes of action for antifungal activities in a simple, sensitive, time and cost effective manner. Significance and Impact of the Study: A simple fluorescence‐based high throughput method is developed to test the effects of stress and antifungal agents on viability of filamentous fungus Magnaporthe oryzae . This resazurin fluorescence assay can detect inhibitory effects comparable to those obtained using the growth inhibition assay with added advantages of simplicity, time and cost effectiveness. This high throughput viability assay has a great potential in large‐scale screening of the chemical libraries of antifungal agents, for evaluating the effects of environmental conditions and hyphal kinetic studies in mutant and natural populations of filamentous fungi.